2022
DOI: 10.1097/ju.0000000000002798
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Percutaneous Ablation Therapy to Partial Nephrectomy for cT1a Renal Cancers: Results from the Canadian Kidney Cancer Information System

Abstract: Purpose:Percutaneous ablation therapy (AT) and partial nephrectomy (PN) are successful management strategies for T1a renal cancer. Our objective was to compare AT to PN with respect to recurrence-free survival (RFS) and overall survival (OS).Materials and Methods:Patients post PN or AT for cT1aN0M0 renal cancer from 2011 – 2021 were identified from the national Canadian Kidney Cancer Information System (CKCis). Inverse probability of treatment weighting (IPTW) using propensity scores (PS) was used. The primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 30 publications
(71 reference statements)
0
9
0
Order By: Relevance
“…22 Nevertheless, 2 contemporary large-scale analyses with pathologically confirmed T1a RCC reported higher recurrence-free survival and lower CSM after partial nephrectomy vs local tumor destruction. 23,24 To the best of our knowledge, our findings regarding higher CSM after hTA vs CA in patients with tumor size 3.1-4 cm can only be partially compared with Palumbo et al (SEER 2004(SEER -2015 CA vs 217 hTA), who also reported higher CSM rates (7.6% vs 3.9%, P [ .02) after hTA vs CA. 5 The limitations in comparison between the 2 studies are based on several considerations.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…22 Nevertheless, 2 contemporary large-scale analyses with pathologically confirmed T1a RCC reported higher recurrence-free survival and lower CSM after partial nephrectomy vs local tumor destruction. 23,24 To the best of our knowledge, our findings regarding higher CSM after hTA vs CA in patients with tumor size 3.1-4 cm can only be partially compared with Palumbo et al (SEER 2004(SEER -2015 CA vs 217 hTA), who also reported higher CSM rates (7.6% vs 3.9%, P [ .02) after hTA vs CA. 5 The limitations in comparison between the 2 studies are based on several considerations.…”
Section: Discussionmentioning
confidence: 50%
“…22 Nevertheless, 2 contemporary large-scale analyses with pathologically confirmed T1a RCC reported higher recurrence-free survival and lower CSM after partial nephrectomy vs local tumor destruction. 23,24…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the Editor: We read with great interest the publication by Millan et al comparing percutaneous ablation therapy to partial nephrectomy as a treatment for cT1a renal cancers. 1 This national multicenter prospective cohort included 2,276 patients from the Canadian Kidney Cancer Information System from 2011 to 2021, and analyzed the recurrence-free survival and overall survival (OS) with propensity score techniques to adjust the differences between the groups. This publication provides more convincing evidence regarding the outcome of the treatment for cT1a renal cancers.…”
mentioning
confidence: 99%
“…Patients requiring systemic therapy (metastases) will likely have significantly worse prognoses than those with cT1a RCC; however, our data set is underpowered to comment on outcomes of patients subsequently requiring extirpative surgery after AT (13 in the AT cohort and 18 in the PN cohort). 1,7…”
mentioning
confidence: 99%